Understanding readers movements in www documents - Cossío, María González de (InfoDesign, 2004)
The aim of this study is to know readers' movements in electronic space. The complete work is structured as a journey through the World Wide Web (www) environment, constituted by the description of graphic, navigation and organisational elements, readers' methods of manipulation within a web site and mental models readers develop whilst navigating in the web environment. Knowledge of navigation in physical space provides a theoretical framework to study readers' movements in web environments. The stages in acquiring spatial knowledge (landmark-route-survey) are examined and tested. Results suggest that when readers interact with web documents they recall graphic elements as landmarks. Readers develop route knowledge of well-known documents. Readers do not seem to develop survey knowledge or cognitive maps from the tests done. Finally, the author suggests that traversing web documents should be considered as semantic navigation rather than spatial navigation. In this article the author only describes the studies conducted to discover whether readers develop route and survey knowledge in well-known www documents.